The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1371/journal.pone.0274836
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrated community-facility interventions model on neonatal mortality in rural Bangladesh- a quasi-experimental study

Abstract: Background Neonatal mortality remains unacceptably high in many countries. WHO recommends that all newborns be assessed during the postnatal period and should seek prompt medical care if there is any danger sign. However, in many developing countries, only a small proportion of women receive postnatal care. Also, the quality of care in public health facilities is sub-optimal. Methods We designed an intervention package that included community health worker-assisted pregnancy and birth surveillance, post-nata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
(69 reference statements)
0
2
0
Order By: Relevance
“… 57 , 58 , 59 Management of very small and sick newborns in newborn intensive care units of hospitals has been found to improve survival, but issues of access and quality persist in low-resource settings. 60 , 61 , 62 , 63 A recent study in Sylhet region of Bangladesh assessed the effect of integrating a community-facility intervention model, which included inputs to improve the quality of neonatal care at the first-level referral facility and used the existing CHW surveillance system in the study area to identify and refer sick newborns. Investigators found that the integrated model resulted in early identification and timely referral of severely ill newborns; increased care-seeking; improved treatment; and overall reductions in case fatality and neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 , 58 , 59 Management of very small and sick newborns in newborn intensive care units of hospitals has been found to improve survival, but issues of access and quality persist in low-resource settings. 60 , 61 , 62 , 63 A recent study in Sylhet region of Bangladesh assessed the effect of integrating a community-facility intervention model, which included inputs to improve the quality of neonatal care at the first-level referral facility and used the existing CHW surveillance system in the study area to identify and refer sick newborns. Investigators found that the integrated model resulted in early identification and timely referral of severely ill newborns; increased care-seeking; improved treatment; and overall reductions in case fatality and neonatal mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators found that the integrated model resulted in early identification and timely referral of severely ill newborns; increased care-seeking; improved treatment; and overall reductions in case fatality and neonatal mortality. 61 In addition to improving the quality of facility-based care for neonates, greater investment is needed in community-facility strategies to improve timely identification and referral of severely ill babies to upgraded facilities. Our findings suggest that these gains in survival for small, vulnerable newborns may extend beyond the neonatal period.…”
Section: Discussionmentioning
confidence: 99%